Systematic analysis of bypass suppression of essential genes. Issue 9 (17th September 2020) - van Leeuwen, Jolanda; Pons, Carles; Tan, Guihong; Wang, Jason Zi; Hou, Jing; Weile, Jochen; Gebbia, Marinella; Liang, Wendy; Shuteriqi, Ermira; Li, Zhijian; Lopes, Maykel; Ušaj, Matej; et al.
Abstract: Essential genes tend to be highly conserved across eukaryotes, but, in some cases, their critical roles can be bypassed through genetic rewiring. From a systematic analysis of 728 different essential yeast genes, we discovered that 124 (17%) were dispensable essential genes. Through whole‐genome sequencing and detailed genetic analysis, we investigated the genetic interactions and genome alterations underlying bypass suppression. Dispensable essential genes often had paralogs, were enriched for genes encoding membrane‐associated proteins, and were depleted for members of protein complexes. Functionally related genes frequently drove the bypass suppression interactions. These gene properties were predictive of essential gene dispensability and of specific suppressors among hundreds of genes on aneuploid chromosomes. Our findings identify yeast's core essential gene set and reveal that the properties of dispensable essential genes are conserved from yeast to human cells, correlating with human genes that display cell line‐specific essentiality in the Cancer Dependency Map (DepMap) project. Synopsis: A systematic analysis of 728 different essential yeast genes identifies 124 (17%) dispensable essential genes. Whole‐genome sequencing is used to identify the genome alterations underlying the bypass suppression. Dispensable essential genes show distinct properties that can be used to predict essential gene dispensability and are conserved from yeast to human cells. Bypass suppressors often show a strong functional connection to the dispensable essential gene, which can be used to predict suppressor genes. Dispensable essential genes can generally only be suppressed by a single genetic mechanism, including aneuploidies and mutations in specific suppressor genes, which involve both loss‐of-function and gain‐of-function alleles. A list of 805 core essential genes is defined that are either absolutely required for cell viability in yeast or only suppressed by highly complex genetic mechanisms. Abstract : A systematic analysis of 728 different essential yeast genes identifies 124 (17%) dispensable essential genes. Whole‐genome sequencing is used to identify the genome alterations underlying the bypass suppression.